Portable-2WG: Water and Wind Portable Power Plant for Electricity Needs of River Flow Residents - Yulia Yulia; João Victor Pequeno de Oliveira (Journal Electrical and Computer Experiences, 2025)
Indonesia is a country consisting of 70% of the territory of water. This causes Indonesia to have a potential energy of the wind of 9.29 GW. In addition, Indonesia also has high rainfall that is 2000-3000 mm / year provides water potential of 75.65 GW. In line with the increase in the electrical ratio target to 100% by 2025, the electricity is projected to increase more than 7 times to 1,611 Twh by 2050. As a solution of high electricity consumption, then created Portable-2WG (Portable Energy from Photovoltaic and Wind Water Generator). Portable-2WG is a combination of a turbine and solar panel, where this turbine is designed to be used to convert wind and water power. When the dry season, this turbine will be functioned as a vertical wind turbine with to utilize the potential of the abundant wind energy in the dry season. While the rainy season, turbine can be functioned as floating water turbine so that the utilization of potential water can be optimal.